A SURVEY ON ELEMENTARY SCHOOL BULLYING - Julia Urba Swastika (MEDIA DAN STRATEGI PEMBELAJARAN, 2025)
This research purpose is to map the potential for bullying in a review of school activities, including physical, verbal, relational, and cyberbullying. Data was collected using a quantitative survey base with 1068 respondents in one sub-district by distributing questionnaires. The results of the research show that the experience of bullying in elementary schools is relatively low; on average, 38.2% of children experience bullying, which is dominated by verbal bullying. Meanwhile, physical bullying was 19.8%, and relational bullying was 17%. The data above shows that bullying is actually experienced by elementary school students, but it can still be controlled and is not yet at a dangerous stage